Dampak Sosialisasi Hukum Perlindungan Perempuan Terhadap Tingkat Pelaporan Kasus Kekerasan Dalam Rumah Tangga (KDRT) - Shafira Yunda Maharani; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The legal issue of protecting women from domestic violence (DV) is an important concern in law enforcement efforts in Indonesia. The high number of unreported domestic violence cases indicates that there are significant obstacles in the reporting process, one of which is caused by women's lack of understanding of their legal rights. The socialization of women's protection laws is expected to increase women's awareness and courage to report domestic violence cases. This study aims to analyze the impact of socialization of women's protection law on the reporting rate of domestic violence cases. The writing method used is normative juridical with legislative approach and conceptual analysis. Data is obtained through literature study of related laws and regulations, such as Law Number 23 Year 2004 on the Elimination of Domestic Violence. The results show that legal socialization has a positive impact on increasing the reporting rate of domestic violence cases. Effective socialization not only increases women's knowledge of their rights, but also strengthens the emotional and psychological support needed to report the violence experienced. However, the results also revealed that structural barriers such as social stigma, fear of retaliation, and lack of support from law enforcement are still major obstacles. Therefore, continuous efforts are needed to improve the quality and reach of legal socialization, as well as to improve the legal protection system that is more responsive to the needs of women victims of domestic violence.